Synthesis of fluorescent carbon quantum dots from Jatropha fruits and their application in fluorometric sensor for the detection of chlorpyrifos - Chandra S.; Bano D.; Sahoo K.; Kumar D.; Kumar V.; Kumar Yadav P.; Hadi Hasan S. (My University, 2025)
In this study, we have synthesized fluorescent carbon quantum dots (J-CQDs) from Jatropha fruit by using a one-pot hydrothermal approach, for the first time. The as-synthesized J–CQDs exhibited bright blue fluorescence emission with a high quantum yield of 13.7 %. Furthermore, the synthesized fluorescent J-CQDs have been used as a fluorometric sensor for the detection of pesticides. The sensing of pesticides is based on the irreversible catalytic inhibition of acetylcholinesterase (AChE) enzyme with a controlled fluorescence quenching process. The thiocholine was mainly triggered by the decomposition of DTNB to form yellow-colored TNBA. Further, TNBA gradually quenched the fluorescence emission spectra of added J-CQDs via dynamic quenching. The catalytic activity of AChE was inhibited in the presence of OPs, leading to the recovery of the fluorescence signal. Thus, a sensitive and selective nanoprobe was designed for the sensing of OPs (chlorpyrifos) along with a detection limit 2.7 ng/mL. Apart from this, the proposed sensing method has been successfully applied for pesticide detection in environmental and agricultural samples with acceptable recovery. Thus, the delivered result suggests that our probe is simple in design, having a short reaction time, and could be proficiently used in further analytical and environmental applications in the future. © 2021